Do sub-doses of glyphosate and 2,4-D cause hormesis in the pineapple plants? Insights into the response of the pineapple plants to this phenomenon - Barreto, Glauber Ferreira; Arcanjo Alves , José Maria; Ribeiro Rocha, Paulo Roberto; Santiago Castro, Thaís; Oliveira da Silva , Deyse Cristina; Sonicley da Silva Maia, Sonicley; a Alves de Albuquerque, José de Anchieta; Torres de Souza, Leandro (Comunicata Scientiae, 2024)
The slow growth of the pineapple (Ananas comosus (L.) Merr.) during the vegetative phase prolongs the crop cycle, resulting in higher production costs. When used in low doses, some herbicides can stimulate plant growth, a phenomenon known as hormesis. The aim of this study was to determine the effects of sub-doses of glyphosate and 2,4-dichlorophenoxyacetic acid (2,4-D) on growth in the Pérola cultivar of the pineapple. The treatments under study consisted of glyphosate applications of 0, 1.8, 3.6, 7.2, 18, 36, 72, 180, 360 and 720 g a.e. ha-1, and 2,4-D applications of 0, 1.68, 3.35, 6.70, 16.75, 33.5, 67, 167.5, 335 and 670 g a.e. ha-1. The experiments were completely randomised with four replications. The plants were grown in the greenhouse in pots with a capacity of 8 dm3 substrate. Growth variables were evaluated in the plants, together with the total and partitioned accumulated biomass (leaf, stem and root). The data were submitted to analysis of variance and regression. The pineapple showed greater phytotoxicity from the glyphosate herbicide at applications ranging from 18 to 720 g a.e. ha-1 and from 2,4-D in the range of 167.5 to 670 g a.e. ha-1. The hormesis effect was evidenced by the 32.25% increase in root fresh weight at the dose of 1.8 g a.e. ha-1 glyphosate. However, the slow growth of the pineapple was not overcome by the hormesis effect of the herbicides.